Impact of Import Thrifting in Indonesia: A Case Study on Used Fashion Products - Yoliandri Nur Sharky (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Importing used clothing has become a controversial topic in recent years. Some see it as a good solution to fight poverty and promote resource saving, while others see it as a practice that is detrimental to the clothing industry and the environment. On one occasion, I will discuss the first, why thrifting used clothing is in great demand by the public, then, second, is there a legal basis for prohibiting the import of used clothing, after that, third, is there any negative impact from buying used clothing. Because at this time Thrifting has become a fashion product that is in great demand because of its very affordable prices, attractive models, and of course it has a brand label from abroad. However, the Trade Law and the Regulation of the Minister of Trade have given a warning that actually importers may not import used goods, clothing that is not suitable for use. And if you violate it, you will be subject to sanctions in the form of 5 years imprisonment and or a fine of 5 billion. Therefore, importers and the public are urged not to buy imported used clothes and to support domestic industries that are no less good.